The Impact of Alcohol on Male Fertility - Bohra, Nishrin; Agrawal, Poornima; Joshi, Jishi; Gandhi, Pooja; Gaur, Kalpesh; Rathore, Mahendra Singh (Indian Journal of Pharmacy Practice)
The study is based on evaluation of impact on sperm quality due to alcohol at tertiary care hospital. There are many risks involved due to addictive substances like alcohol were observed and the data of overall study proves the significant results. Materials and Methods: A non-interventional prospective observational study of six months duration was carried out on outpatients qualifying inclusion criteria. The socio-demographic details, alcohol history, type of beverages and frequency was collected in a specialized data collection. Data collected was analyzed with MS EXCEL sheet and data were represented as mean, standard deviation, p-value, and percentages. Results: Out of 246 majorities of patients 53.25% were in the age group of 28-37 years. The patient who was alcoholic (39.8%) and non-alcoholic (60.1%). The lab parameter for alcoholic were compared to non-alcoholic which elucidates significant difference (p<0.001) that effect the sperm quality. The type of alcoholic beverages was studied where the increase of types results in decrease of semen parameter the significance (p<0.05). The frequency was measured as mild(monthly), moderate(weekly), and severe(daily) the various parameters show significant difference in value with increased. According to WHO-semen analysis parameters were evaluated. Conclusion: The alcohol consumption was observed as the patterns of types of beverages used and frequency of consumption and that leads to the result that it affects the morphology of sperm and increases the risk of sterility.
Keywords: Alcohol; Male Sterility; Morphology defect; Motility; Semen Parameter